SWITCHING CODES AND MIXING CODE AT 9 YEARS OLD CHILDREN'S COMMUNICATION - Saragih, Sanju Febrio; Damanik, Bernieke Anggita Ristia (Cahaya Ilmu Bangsa Institute, 2025)
This study examines the phenomena of code switching and code mixing among bilingual children, focusing on a 9-year-old Indonesian child, Gracia. Using a qualitative approach, the research identifies patterns and functions of these linguistic practices in daily communication. The findings reveal that code switching and code mixing facilitate expression, social adaptation, and emotional communication, influenced by bilingual exposure, pop culture, and situational contexts. While these phenomena enhance cognitive abilities and cultural adaptability, they may challenge linguistic mastery if overused. The study contributes to understanding bilingual language development, with implications for multilingual education in Indonesia.